The strategy for permanent training of professors in the Medicine career for attention to cultural diversity - González Alonso , José Ángel; Carballosa González , Ania; Díaz Quiñones, José Aurelio (Revista Minerva, 2023)
The permanent training of the professors of the Medicine career for the attention to the cultural diversity, constitutes a priority, in responding to the educational needs of the students, in correspondence with the demands of the intercultural principles and of the didactics, contextualized to Higher Medical Education. The objective of the research was: to develop a permanent training strategy aimed at professors of the Medicine career for attention to cultural diversity. In its elaboration, theoretical methods such as the analytical synthetic, inductive-deductive and the system approach were used and among the empirical methods the analysis of documents, participant observation and the interview. The results of the application of the training strategy in practice from a system of workshops, demonstrated its validity, applicability and relevance, as well as high levels of satisfaction in teachers for the preparation received. By way of conclusion, the proposal allowed to address theoretical, methodological and conceptual aspects to overcome the inadequacies diagnosed in teachers regarding their professional pedagogical performance in intercultural education in the various contexts.
Keywords: Permanent training; Intercultural Education; attention to cultural diversity; Medical Education; intercultural and didactic principles.